Non‐genetic biomarkers and colorectal cancer risk: Umbrella review and evidence triangulation - Xiaomeng Zhang; Dipender Gill; Yazhou He; Tian Yang; Xue Li; Grace Monori; Harry Campbell; Malcolm Dunlop; Konstantinos K. Tsilidis; Maria Timofeeva; Evropi Theodoratou (Cancer Medicine)
Abstract Several associations between non‐genetic biomarkers and colorectal cancer (CRC) risk have been detected, but the strength of evidence and the direction of associations are not confirmed. We aimed to evaluate the evidence of these associations and integrate results from different approaches to assess causal inference. We searched Medline and Embase for meta‐analyses of observational studies, meta‐analyses of randomized clinical trials (RCTs), and Mendelian randomization (MR) studies measuring the associations between non‐genetic biomarkers and CRC risk and meta‐analyses of RCTs on supplementary micronutrients. We repeated the meta‐analyses using random‐effects models and categorized the evidence based on predefined criteria. We described each MR study and evaluated their credibility. Seventy‐two meta‐analyses of observational studies and 18 MR studies on non‐genetic biomarkers and six meta‐analyses of RCTs on micronutrient intake and CRC risk considering 65, 42, and five unique associations, respectively, were identified. No meta‐analyses of RCTs on blood level biomarkers have been found. None of the associations were classified as convincing or highly suggestive, three were classified as suggestive, and 26 were classified as weak. For three biomarkers explored in MR studies, there was evidence of causality and seven were classified as likely noncausal. For the first time, results from both observational and MR studies were integrated by triangulating the evidence for a wide variety of non‐genetic biomarkers and CRC risk. At blood level, lower vitamin D, higher homeostatic model assessment‐insulin resistance, and human papillomavirus infection were associated with higher CRC risk while increased linoleic acid and oleic acid and decreased arachidonic acid were likely causally associated with lower CRC risk. No association was found convincing in both study types.